Detection of a new case of Down-Turner mosaicism (45,X/47,XY,+21) in a patient with psoriasis vulgaris. - Angelova, L.; Kovatcheva, K.; Simeonova, M.; Angelova, S.; Trashlieva-Koicheva, M. (European Journal of Pediatric Dermatology, 1997)
A new case of Down-Turner syndrome in a male with 45,X/47,XY,+21 mosaicism is described. He displays a constellation of clinical features characteristic of either syndrome with predominant stigmata of Down syndrome. Cytogenetic investigation of leucocyte preparations revealed two stem lines of cells, 47,XY,+21 and 45,X in close proportions. Unusually for the syndrome, the patient had been suffering for many years and diagnosed as having the most common clinical type of plaque forming psoriasis, recently presenting firm evidence of genetic components. Dermatologists may observe Down-Turner syndrome occasionally, but they should recognize it at young age because of possible coincident coexistence with psoriasis if not a significant association.